MENDISKUSIKAN PIDANA PERS TERHADAP ISI BERITA YANG BERMUATAN PENCEMARAN NAMA BAIK DI KORAN - Nur Aida Akbari (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2018)
The press is an institution that has a strong influence in disseminating news presented in the newspaper. Unfortunately, criminal defamation elements have frequently been found in the news presented to public. The acts can be sued based on criminal law. The parties who are responsible for such acts must also be sentenced based on the criminal liability system.